The impact of multiple project team membership on individual and team learning: A micro-meso multi-level empirical study. Issue 3 (April 2021) - Chan, Kai-Ying; Oerlemans, Leon; Meslec, Nicoleta
Highlights: Multiple project team membership variety is positively correlated to individual learning. The need for cognition moderates the relation between multiple project team membership variety and individual learning. Inter-organizational project team membership is positively correlated to external team learning. Intra-organizational membership negatively moderates the relation between inter-organizational project team membership and external team learning. Individual learning is positively correlated with internal and external team learning. Abstract: In this paper, we investigate the effects of multiple project team membership on individual and team learning. Data from 435 members of 85 project teams shows that, at the individual level, membership variety has a positive impact on individual learning. Moreover, this positive relationship is stronger for individuals with an average need for cognition, in comparison to individuals with a high or a low need for cognition. At the project team level, the simultaneous inter-organizational memberships of a project team have a positive impact on the team's external learning. However, the simultaneous intra-organizational project team memberships negatively moderate this positive relationship. Furthermore, cross-level analyses show that individual learning has a positive impact on both internal and external team learning. Our findings are relevant for project management practice as they suggest ways in which work design can be configured to increase individual and team learning.